PENGARUH KEMAMPUAN KOMUNIKASI DAN DISIPLIN BELAJAR SISWA TERHADAP HASIL BELAJAR MATA PELAJARAN HUBUNGAN MASYARAKAT KELAS XII ADMINISTRASI PERKANTORAN SMK N 1 BANYUDONO - Gemawati Gemawati; Wiedy Murtini; Tri Murwaningsih (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2019)
The objectives of this study were to direct (1) the effect of communication skills on learning outcomes of public relations subject of grade XII AP SMK N 1 Banyudono, (2) the effect of student learning discipline on learning outcomes on public relations, (3) the effect of communication skills and student learning discipline on learning outcomes of public relations subject. This research used quantitative methods. The population was all students of grade XII. Sample of 71 students were taken by census technique. Data collection techniques for communication skills, learning discipline used questionnaire method, while learning outcomes used documentation method. The data analysis technique used was multiple regression analysis using SPSS 17. Based on the results of data analysis that have been carried out, (1) there is a significant effect of communication skills on learning outcomes, (2) there is a significant effect of learning discipline on learning outcomes, (3) there is a significant simultaneous effect of communication skills and learning discipline on learning outcomes. With the effective contribution of communication skills (X1) of 17%, the effective contribution of learning discipline (X2) of 23.2% and the relative contribution of communication skills (X1) of 43.33%, the contribution of relative learning discipline (X2) of 56.71%.